Loneliness and Cardiovascular Disease - Agarwal, Shashi K. (International Journal of Medicine, 2021)
Loneliness is a silent social epidemic that affects more than one third of the US population. Cardiovascular diseases impart a huge morbidity, mortality, and financial burden on our society. The detrimental role of loneliness in cardiovascular diseases is being increasingly recognized. Besides having a direct molecular effect on cardiovascular diseases, loneliness also encourages poor compliance with healthy lifestyles, that play a significant role in preventing and improving cardiovascular diseases. This brief review highlights the ominous effects of loneliness on cardiovascular diseases.